Penatalaksanaan Erisipelas pada Pasien Dewasa Usia 42 Tahun Melalui Pendekatan Dokter Keluarga - Reni Zuraida; Vermitia (CV. Jasa Sukses Abadi, 2020)
Erysipelas is a relatively common infectious disease of the skin form of erythema which is clearly demarcated with elevated margins with signs of acute inflammation. The incidence of erysipelas in 2012 in Surabaya was 14 cases with the most cases in women and in the age group 45-64 years. Erysipelas is a disease that can be treated in primary health care facilities or general practice. But there are risk factors for this disease that cause frequent cases of recurrent erysipelas so that proper management is needed. This study is a case report which aims to identify internal and external risk factors and clinical problems in patients, as well as holistically manage patients by applying family doctors according to evidence based medicine through a patient centered approach and family approach. Primary data were obtained through history taking (autoanamnesis from patient and alloanamnesis from patient's family) physical examination and home visits. Secondary data were obtained from the patient's medical record. Assessment is based on a holistic diagnosis from the beginning, process, and end of study in a qualitative and quantitative manner. Patient Mr. W age 42 years old has been diagnosed with erysipelas having concerns about health conditions that are considered to interfere with his work and daily activities. Limitations on the patient's knowledge of the disease (cause, mode of transmission, risk factors, treatment, and complications). In addition, patients pay little attention to personal hygiene, especially related to the risk of hygiene in their work. Holistic and comprehensive management of patients' problems Mr. W has been done by providing counseling to improve patient and family knowledge of erysipelas.